Building Intelligent Information Systems Software : Introducing the Unit Modeler Development Technology - Feigenbaum, Thomas D.; ScienceDirect eBooks (Morgan Kaufmann, 2015)
Building Intelligent Information Systems Software shows scientists and engineers how to build applications that model complex information, data, and knowledge without the need for coding. Traditional software development takes time and leads to inflexible, complicated applications that almost, but don't exactly, meet the intended needs. Requirements can change, sometimes mid-development, and adapting existing systems can be difficult. Individual solutions can be incompatible, leading to information silos and inefficiency throughout an organization. This book offers a solution - the Information Unit Model, an innovative architecture for translating domain knowledge into applications. By encapsulating the complexities of computing, the Unit Model allows engineers to focus on business or experimental needs. Author Tom Feigenbaum, inventor of the Unit Modeler, demonstrates this innovative software architecture for rapid application design and development. His approach promotes repurposing pre-existing tools and libraries, and collaborating across the cloud, to promote information sharing and efficient development practices. Each concept is illustrated with examples including file management, data management, and 3D visualization.
Test Creator: encapsulation exampleReuse of models; Finding reusable components; Mechanisms for reusing components; Assists in the Development Resource Center; Creating a class instance; Class attributes; Areas of support; Modeling Structures; Classes; Processes; Elements; Loops; Decision points; Getting information; Unit manipulation; Lists; Computer technology; Forms/graphical user interfaces; Showing forms; Printing; Visualizations; Overview; The graph class; Tools; Assists; Custom plots; Animation; Video; Databases; Web services; Network communication; File manipulation.
Elsevier
Keywords: Computer software -- Development; Model-driven software architecture; Software architecture -- Methods; Computer software -- Development; Model-driven software architecture; Software architecture; Electronic books